Prospects for the Use of Information and Communication Technologies in the Provision of New Types of Insurance in the Republic of Uzbekistan - A. B. Abdusalomov (Статистика и экономика)
This article is devoted to the issues of effective application of advanced information and communication technologies in the insurance activities of the Republic of Uzbekistan. The author, using the example of the “Ishonch” insurance company, shows that in the modern period in the Republic of Uzbekistan the quality of the provision of insurance services is improving, as well as their quantitative indicators are growing.Purpose. The purpose of this article is to scientifically substantiate the place and role of advanced information and communication technologies in the provision of insurance services in the economic market, as well as the development of the insurance sector in the context of the development of the digital economy.Materials and methods. In the course of preparing the material for this article, the methods of system analysis, economic and mathematical methods and models, special methods of working with information systems and computer networks of various levels were used. All materials of the article are based on the use of factual material of the insurance company “Ishonch” of the Republic of Uzbekistan.Results. The article presents the author's approaches to the development of a distributed management system for the web resources of an insurance company in the global computer network of the Internet, it is proved that in the modern period the effectiveness of the functioning of insurance companies in the economic market depends on the degree of implementation of advanced information and communication technologies in their activities.In this paper, it is emphasized that the use of advanced information and communication technologies is of great importance in the development of insurance activities. In particular, the author emphasizes that the development of insurance services is achieved both by the development of existing software products, and by the development of new technological, software and information solutions based on the introduction of digital technologies.This paper shows that an information system is of great importance for the effective functioning of an insurance company, which includes a complex of interrelated subsystems providing the effective functioning of an insurance company in the economic market.Particular importance in this article is given to the use of the global Internet network. The author noted that the web representation of the insurance company on the Internet and the use of platform solutions and cloud technologies play a large role in the company's activities. In addition, the article tells about the fact that recently in the insurance business, electronic business is becoming widespread, which allows you to link together all participants in the insurance market.Conclusion. The material of this article shows that in the modern period in the insurance activities of the Republic of Uzbekistan there is a continuous process of introducing advanced information and communication technologies, contributing to the development of both the insurance sector itself and all participants in the economic market through the use of information systems, technologies, software products and new electronic services being introduced.The article notes that modern insurance companies, thanks to the development of advanced information and communication technologies, work with their clients directly, which creates benefits for both clients and insurance companies. In general, this article shows that the development of insurance activities in modern conditions is unthinkable without the use of advanced information and communication technologies and the adoption of competent management decisions.